Integrative taxonomic re-description of Halisarca magellanica and description of a new species of Halisarca (Porifera, Demospongiae) from Chilean Patagonia - Willenz, Philippe; Ereskovsky, Alexander V.; Lavrov, Dennis V. (Zootaxa, 2016)
A series of recent expeditions in fjords and canals of Southern Chilean Patagonia allowed the re-collection of Halisarca magellanica Topsent, 1901 and the discovery of a new species, Halisarca desqueyrouxae sp. nov. The material studied was collected at depths ranging from 3 to 30 m at latitudes comprised between 42° and 49°S. Both species share the same habitat and show a morphological plasticity, but differ in their colour. Halisarca magellanica is bright pink to whitish with three morphs whereas H. desqueyrouxae sp. nov. is light brown to beige with two morphs. An extensive investigation in TEM and SEM reveals several differences among cell types with inclusions between both species. Three distinct spherulous cells occur. Type 1 is shared by both species, Type 2 is occasional in H. magellanica but absent from H. desqueyrouxae sp. nov. Type 3 is rare in H. magellanica and occurs abundantly in half of the specimens of H. desqueyrouxae sp. nov. Granular cells are shared by both species but do not occur in all specimens. Microgranular cells are characteristic of H. magellanica. Both species also clearly differ by their endobiotic bacteria. Phylogenetic analysis of cox1 sequences places H. magellanica as a sister group to all other previously published Halisarca species sequences (9.1–9.7% difference) except H. harmelini, while H. desqueyrouxae sp. nov. is placed as a sister group to H. dujardini (2.3% difference).